Pengaruh Model Problem Based Learning Terhadap Motivasi Belajar Peserta Didik SMA Negeri 1 Panawangan - Syahid Faturrojak; Dewi Septiani Kurniasih (Lembaga Pengembangan Kinerja Dosen, 2022)
Underachieving students are not caused by their lack of ability, but can be caused by a lack of motivation to learn. The purpose of this research is to increase students' learning motivation through the application of the Problem Based Learning model. The research was conducted quantitatively using a descriptive survey method. The results of this study indicate that efforts to apply the Problem Based Learning learning model which is supported by giving appreciation or awards to students have been able to stimulate students' learning motivation.